Importance of the cyst-urethrography in the treatment of stress urinary incontinence - Arenas, Normando (2015)
The urethrocystography enhanced value in diagnosis of stress incontinence. It has been make a description of the employed technique that was used . In 20 woman patients the most important complaint was the low urethrovesical junction, less frequently was funneling of the urethra with loss of the posterior angle under stress. In lateral projection there was an increased angle over 110° in the 55% patients without micturition and 70% with stress. In 4 patients was made the urethrocystography after operation and it is important to think not always is necessary in the treatment for stress incontinence to elevate the urethrovesical junction.